ANALYSIS THE DEVELOPMENT OF EXTREME SPORT SKATEBOARD AS SPORTS TOURISM IN KENDAL - Muhammad Setyaki Kurnia Ramadhani; Nanang Indardi (Nusa Cendana University, 2022)
Skateboarding is an urban sport in the United States with a street culture that is one of the extreme sports groups that is growing rapidly among teenagers. The research target is DISPORAPAR, community leader, local communities. Purpose research is for knowing the development of extreme skateboarding as a recreational sport in Kendal Regency. This research used qualitative method. This research instrument uses data collection methods used by researchers with observation guidelines, direct interviews, and documentation, checking the validity of the data in this study using triangulation and member check techniques. Data analysis in this study using data reduction, data presentation and conclusions. The results of research on the development of skateboarding are widely known by the public, but especially for adults and children, they tend not to be interested in trying it. Then the supporting factors include funding, facilities and infrastructure. These two elements are indispensable for the sport of skateboarding to be controlled more advanced